SISTEM INFORMASI GEOGRAFIS GUNA PEMETAAN DATA KEJADIAN PENYAKIT UNTUK KEPERLUAN SURVEILANS DAN KEWASPADAAN DINI DI WILAYAH KERJA DINAS KESEHATAN KOTA SEMARANG - Arif Kurniadi (JURNAL DIAN, 2011)
Disease prevention and eradication programs in the city of Semarang are most effective when supported by an active surveillance system. Presentation of data in the form of spatial datais one form of presentation and interpretation of data. The purpose of this study was to map the incidence of disease for purposes ofsurveillance and early warning of disease incidence for the city ofSemarang, fast and efficient. The research method used is prototype method.Steps being taken are indentifier user needs, develop prototypes,to determine whether the prototype is acceptable, and using the prototype.The design shows ageographic mapping system with staining in a region where interpret incidence of a disease condition in the interpret incidence of a drisease condition in the area inseveral caregories. Category is low in green, medium yellow color, and high in red. Map of Semarang City area includes map of the village,District, PHC and maps describing the condition of the entire working area of Health Distric Semarang.